Establishment of an In Vitro Micropropagation System for Cannabis sativa ‘Cheungsam’ - Sang-Cheol Baek; Sang-Yoon Jeon; Yoon-Jung Choi; Bo-Hyun Byun; Da-Hoon Kim; Ga-Ram Yu; Hyuck Kim; Dong-Woo Lim (Horticulturae)
Cannabis has been cultivated for thousands of years for a variety of purposes, including fiber, seeds, oil, and medicinal compounds. The cannabis industry is growing rapidly because several countries have recently legalized the use of cannabis. In these countries, the industry related to cannabinoid ingredients such as cannabidiol (CBD) and Δ9-tetrahydrocannabinol (THC) is steadily increasing every year. High concentrations of cannabinoids are mainly produced in unfertilized female flowers. Maintaining plants with high cannabinoid content is essential for producing uniform substances in large quantities. This study established an in vitro micropropagation protocol that can maintain the mother plant characteristics of Cannabis sativa ‘Cheungsam’. As a result of this experiment, the shoot tips and nodes of Cannabis sativa ‘Cheungsam’ at various concentrations (0, 0.25, 0.5, 1.0 mg/L) of 2iP, BA, and mT plant growth regulators (PGRs), and all concentrations of 2iP showed better results compared to two other hormones. However, the cut surfaces turned black, and excessive hyperhydricity occurred. Based on these symptoms, activated charcoal was added to the medium with the assumption that necrosis and hyperhydricity occur due to the accumulation of reactive oxygen species (ROS). When treated with 0.5 g/L charcoal, hyperhydricity was not overcome, and there was no difference compared to the control. As a new alternative, we divided the experiments into MS (Murashige and Skoog) and DKW (Driver and Kuniyuki Walnut) medium, which were commercially available. As a result, the rate of hyperhydricity was reduced, the cut surface did not turn black, and the growth conditions were also improved. Subsequently, ½ MS medium and ½ DKW medium were treated with various concentrations of IBA alone and with combinations of IBA and NAA for rooting. As a result, ½ DKW with IBA 0.5 mg/L showed the highest rooting rate and the best root condition for Cheungsam. After 4 weeks, when considering rooted plants with a height above 5 cm that were acclimatized, the acclimatization rate reached 100%. In conclusion, the Cannabis sativa ‘Cheungsam’ plants used in this study produced healthy shoots on DKW medium containing 1.0 mg/L 2iP and 0.5 mg/L of IBA in ½ DKW medium showed the best rooting rate.